Exploring the Potential of TV 3.0: Applications and Impact on Content Delivery and Audience Engagement - Moraes, Daniel de Sousa; Borges, Paulo Victor; Costa, Polyana Bezerra da; Gurevitz, Yan Martins B.; Santos, Pedro T. Cutrim dos; Boaro, José Matheus Carvalho; Ladele, Adeoye Sunday; Colcher, Sérgio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244583, 2024)
This paper explores potential applications for TV 3.0, a ground-breaking evolution in Brazilian digital television that introduces advanced functionalities such as app-based experience, viewer-centered design, enhanced interactivity, and integration with smart technologies. Leveraging these new capabilities, TV 3.0 can revolutionize content delivery and audience engagement in several key areas by enabling personalized content experiences with recommendations and adaptive streaming to enhance viewer satisfaction and retention. We present three use cases that explore some of the new features and their potential impacts on content transmission and consumption and the development of interactive applications.